2013
DOI: 10.5657/fas.2013.0229
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activities of Chitosan-Phloroglucinol Conjugate

Abstract: In an effort to develop biopolymer-based antioxidant and antibacterial materials, a chitosan-phloroglucinol conjugate was prepared and cellular antioxidant activity and minimum inhibitory concentration against foodborne pathogens and methicillin-resistant Staphylococcus aureus (MRSA) evaluated. The chitosan-phloroglucinol conjugate showed higher antioxidant activities than the unmodified chitosan (P < 0.05). The chitosan-phloroglucinol conjugate showed 62.29% reactive oxygen species scavenging activity, 56.11%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Chang liver cells were grown in a 96-well plate and labeled with 20 μM of 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) dye and left in the dark for 20 min, followed by the addition of 0~0.1 μg/mL of EAF and incubation for 1 h. Thereafter, the cells were washed with PBS, followed by the addition of 650 μM H 2 O 2 to each well. Fluorescence due to oxidative formation of 2′,7′-dichlorofluorescein (DCF) by ROS was measured after 30, 60, and 90 min at excitation and emission wavelengths of 485 and 528 nm, respectively ( 18 ). The percentage of fluorescence intensity (ROS generation) was compared with that of the control cells without the EAF treatment, which were arbitrarily assigned a value of 100%.…”
Section: Materias and Methodsmentioning
confidence: 99%
“…Chang liver cells were grown in a 96-well plate and labeled with 20 μM of 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) dye and left in the dark for 20 min, followed by the addition of 0~0.1 μg/mL of EAF and incubation for 1 h. Thereafter, the cells were washed with PBS, followed by the addition of 650 μM H 2 O 2 to each well. Fluorescence due to oxidative formation of 2′,7′-dichlorofluorescein (DCF) by ROS was measured after 30, 60, and 90 min at excitation and emission wavelengths of 485 and 528 nm, respectively ( 18 ). The percentage of fluorescence intensity (ROS generation) was compared with that of the control cells without the EAF treatment, which were arbitrarily assigned a value of 100%.…”
Section: Materias and Methodsmentioning
confidence: 99%
“…31,40 To enhance water solubility of chitosan by disrupting inter-and intramolecular hydrogen bonding, a number of researchers proposed the synthesis of chitosan derivatives with improved solubility. Their antioxidant activities were proved by experiments conducted in both cell free 13,31,[41][42][43][44] and cell environment.…”
Section: Antioxidant Activities Of Chitosan and Its Derivativesmentioning
confidence: 99%
“…[58][59][60][61] Many studies suggest that due to their redox metabolism, cancer cells are characterized with increased ROS generation, as well as overexpression of antioxidant enzymes in response to the permanent oxidative stress, in comparison to normal cells. 13,[62][63][64][65][66] But at the same time, there are many evidences that have shown that mitochondria and producing ROS are key regulators for induction of cancer cell death. [67][68][69][70][71][72] Natural products have played a pivotal rule in guiding researchers to develop efficient anticancer agents.…”
Section: Anticancer Effects Of Chitosan and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations